Teacher readiness and training needs in implementing content-based instruction - Nakpil, Chielo De La Cruz (2005)
This study aimed to determine the readiness of teachers in implementing Content-Based Instruction (CBI) lessons in their English language classrooms. It utilized survey and classroom observation in its methodology, as well as answers from open-ended interview questionnaire, classroom observation transcripts, and interrater reliability. Results showed that secondary public school teachers were not yet ready for full implementation of CBI due to lack of training, and because they rely primarily on supplied lesson plans and materials which may have some deficiencies. Though curriculum and current trends in language teaching call for contextualization in grammar instruction, grammar is still taught in isolation. One needs to be specific as to what content covers in the language curriculum to avoid misunderstanding in implementing CBI.